Preparation and in vitro evaluation of photodynamic-responsive nanoliposome loaded PL-5 - Wen Lin; Qiong-zhi Shi; Xiang-ru Liao; Yuan Zeng; Xiang-yang Xie; Gang-jian Ji; Yin-ke Li (PLoS ONE, 2026)
Burn wound infections are frequently complicated by biofilm-forming and multidrug-resistant pathogens, particularly methicillin-resistant Staphylococcus aureus (MRSA), posing major therapeutic challenges. Antimicrobial peptides (AMPs) such as PL-5 (peceleganan) exhibit broad-spectrum activity but are limited by instability, poor biofilm penetration, and reduced efficacy in complex wound environments. Here, a red-light-responsive, porphyrin-phospholipid (PoP)-containing cationic liposomal system for PL-5, aiming to enhance its antibacterial and antibiofilm performance was developed. Optimized liposomes achieved high encapsulation efficiency (~73%), uniform nanoscale size (~50 nm), narrow polydispersity, and positive surface charge. They demonstrated good storage stability and controlled peptide release under red-light irradiation (635 nm). In vitro , red-light activation significantly enhanced antimicrobial activity against MRSA and methicillin-susceptible S. aureus (MSSA), reducing minimum inhibitory concentration (MIC) values fourfold and accelerating bactericidal kinetics compared with free PL-5 and non-irradiated liposomes. Additionally, red-light-activated liposomes markedly inhibited biofilm formation. These results indicate that light-responsive liposomal delivery enables spatiotemporally controlled release of PL-5, significantly potentiating its antibacterial and antibiofilm efficacy. This approach offers a promising localized treatment strategy for biofilm-associated burn wound infections and a foundation for future translational studies.